Revegetation of Used Limestone Mining Soil with the Addition of Humic Acid and Limestone Waste - Pratiwi, Dita Irwanti; Nurcholis, Mohammad; Ernawati, Rika (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2024)
PT Akarna Marindo is a limestone mining company located in West Bandung that will carry out revegetation activities with Arabica coffee plants on ex-mining land. PT Akarna Marindo did this by mixing a combination of 5 mm limestone waste from crusher activities and humic acid in Arabica coffee growing media. This research aims to analyze the response of Arabica coffee seedlings to the use of a combination of humic acid and limestone waste. The research used an experimental method with experimental polybags consisting of 5 treatments with 3 repetitions. The response of Arabica coffee seedlings includes seed height and seed diameter. Data processing uses the Analysis of Variance (ANOVA) test. The results of the analysis showed that the response of Arabica coffee seedlings to the combination of 15 mL humic acid and 4 kg limestone waste (A15L4) was an optimal combination of humic acid and limestone waste compared to other treatments in the response of Arabica coffee seedlings. There was an increase in the average height of seedlings from 19.23 cm to 24.90 cm and the diameter of seedling stems from 2.13 mm to 2.53 mm.